Spectrophotometric Determination of Some Adrenergic Drugs Using H2O2 and Dichlorophenolindophenol (Baghdad Science Journal, 2024)
Based on the catalytic response between hydrogen peroxide and dichlorophenolindophenol, a spectrophotometric method was developed to estimate adrenaline hydrochloride  (ADR), Salbutamol sulfate (sal), and dopamine hydrochloride (DOPA) in pharmaceutical preparations. A calculated value of the oxidizing agent (hydrogen peroxide) was added to the basic medium in the presence of dichlorophenolindophenol to form a blue color, which suffers from a bleaching process due to the oxidation process of the drugs mentioned above by the oxidizing agent at λmax 552 nm. The estimated amounts of adrenaline hydrochloride and Salbutamol sulfate were between 0.25 - 5 μg/ml and 0.5 - 5 μg/ml, respectively. The amount of dopamine hydrochloride was between 1 - 7 μg/ml with good sensitivity, as the molar absorbance was 3.8023×104, 8.3506×104and 2.7213×104, respectively. All other statistical values were thoroughly examined. Good agreement with certified value was observed.